The introduction of workplace-based assessment for general surgery training at a South African university - Nel, Daniel (Division of General Surgery, 2026)
Assessment in postgraduate training in South Africa has traditionally focused solely on knowledge objectives. There is currently a movement to introduce Workplace-Based Assessment (WBA) to evaluate trainee clinical competence. However, concerns have been raised regarding the feasibility of this approach in a South African context. Similar concerns about feasibility and other issues with WBA implementation have been identified in General surgery in different settings. The aim of this study was to determine if it was possible to introduce WBA and to identify the characteristics of a WBA strategy that would ensure successful implementation at a South African university. Methods: The design-based research methodology was used to define the educational problem, generate guiding principles for a solution, test the solution through cycles of implementation and refinement, and finally reflect on the implementation process to derive a final set of design principles. The study was conducted in the Division of General Surgery at the University of Cape Town from 2022 to 2023. The planning of the design and the interpretation of the findings were considered in the context of socio-cultural learning theory. Results: Fifteen guiding principles, underpinned by theory, were used to design the WBA strategy. Three cycles of testing and refinement showed relatively high perceived feasibility, acceptability, and appropriateness among trainees and supervisors. The lessons learned from each cycle enabled the solution and design principles to be modified, in consultation with a stakeholder team, to further enhance participant perceptions and implementation. This process resulted in 15 final design principles, of which six were substantive and nine were procedural. The substantive principles related to the selection of EPAs, assessment tools, the supervisor base, and the digital platform. The procedural principles related to the pace of introduction, team development, managing the formative-summative tension, and change management approach. Conclusion: WBA can be introduced for postgraduate General surgery training at a South African university. Design principles have been identified to ensure a feasible introduction in this context. These principles may assist others in implementing new or refining existing WBA strategies.